Örtliches Auslegungskonzept gegen Pittingversagen bei randschichtgehärteten Zahnrädern - Eric, Aleksandar (KIT Scientific Publishing, 2023)
The current design of gears against pitting fatigue is based on simple physical models in combination with empirically determined factors. In contrast to that, this work presents a new design concept against pitting fatigue which is based on local quantities and allows a more detailed consideration of different influence parameters on the expected pitting life.